Analisis Semiotika Logo Ojek Online “INDO-JEK” - Rodiyah diyah; Jupriani Jupriani (DEKAVE : Jurnal Desain Komunikasi Visual, 2021)
In the city of Bangko are one of the motorcycle online that give priority to services between shuttle goods namely Indo-Jek. Indo-Jek once many in the know and many consumers who are interested in using the Indo-Jek. In any company, product, and the public. The research is aimed to describe the shape and know the meaning of the signs that are on logo Indo-Jek, with the approach of semiotics.Research is using method qualitative with analysis of semiotics Charles Sanders Pierce with three element main namely, sign (sign), object, and Interperetant, and to know the meaning of the author using icons, indices, and symbols.In the logo motorcycle online Indo-Jek has characteristics typical of the interesting and different with a motorcycle online in general, things are seen on a logo Indo-Jek which uses the shape of birds to represent his identity. The shape of the bird has  the meaning that the Indo- Jek is a business service that want achieve success as high as with the attitude of trust yourself and give priority to comfort and safety.Kata kunci: Logo, Semiotika, Charles Sanders Pierce, Indo-Jek